Examining Jakarta office mosques: Islamic teaching practices and views of Islamic ideological issues - Ridwan Al-Makassary (IAIN Salatiga, 2013)
This paper discusses Islamic teaching practices and perceptions of mosque stake-holders concerning the ideological issues of: a democratic system of governmentversus formal implementation of Islamic sharia; gender equality; jihad, and plu-ralism in the Jakarta office mosques. After describing the research findings, thepaper concludes that the phenomenon of neo-fundamentalism (in Olivier Roy’swords) is growing and developing in office mosques. This can be seen in thedominance of literal and scripturalist Islamic interpretations, the importance givento implementing Islamic sharia and the rejection of democracy, a hatred of Jewsand Christians and the emergence of Muslim youth actors in Islamic neo-fundamentalism. Other findings concern the influence of the Tarbiyah movement, anoffshoot of the Ikhwanul Muslimin (Muslim Brotherhood), which is being felt inthe office mosques studied. Learning about Islamist understandings will allow usto check its development, which may destroy the friendly, peaceful face of Islam.Paper ini mendiskusikan praktik pengajaran Islam dan persepsi pemangkukepentingan masjid berkaitan dengan isu-isu ideologis: sebuah sistempemerintahan demokratik versus implementasi formal syari’at Islam; kesetaraanjender; jihad, dan pluralism di masjid perkantoran Jakarta. Setelah deskripsitemuan penelitian, paper ini menyimpulkan bahwa fenomena neo-fundamentalisme (meminjam Olivier Roy) sedang tumbuh dan berkembang dimasjid-masjid perkantoran. Ini terlihat dari dominannya intepretasi skripturaldan literal, pentingnya menerima pelaksanaan formal syari’at Islam, kebencianterhadap Yahudi dan Kristen dan kebangkitan aktor-aktor muda fundamentalismeIslam. Temuan lain terkait dengan gerakan Tarbiyah, sebuah anak ideologi IkhwanulMuslimin (Muslim Brotherhood), yang cukup kental ditemukan di masjid yangditeliti. Mengkaji pemahaman Islam akan memungkinkan kita mengawasiperkembangannya, yang mungkin menghancurkan wajah Islam yang ramah dandamai.